Peran Uji Imunohistokimia Postmortem Pada Kematian Jantung Mendadak - Salma Adinda Hermawan; Susianti; Wiwi Febriani; Waluyo Rudiyanto (Medula, 2026)
Routine forensic examinations often fail to establish a definitive diagnosis, particularly in cases of rapid death where no clear macroscopic or microscopic abnormalities are identified. Immunohistochemistry (IHC) is a laboratory technique used to detect the presence and distribution of specific antigens in tissues through antigen–antibody binding combined with specific staining systems. This narrative review discusses the role of postmortem immunohistochemical testing in the evaluation of sudden cardiac death, including examination principles and procedures, forensic applications, relevant immunohistochemical markers, and the influence of the postmortem interval on result interpretation. A literature search was conducted using the PubMed, ScienceDirect, and Google Scholar databases, covering publications from 2016 to 2025. The reviewed studies indicate that postmortem IHC plays a broad role, particularly in cases involving toxic substances, and assists in establishing diagnoses that cannot be determined through routine examinations. Moreover, markers such as troponin, C5b-9, desmin, H-FABP, and CD68 demonstrate diagnostic value in identifying myocardial injury, tissue necrosis, inflammatory processes, and atherosclerotic plaque formation. However, the reliability of IHC findings is influenced by technical factors, including the interval between death and tissue sampling, tissue fixation methods, and variations in laboratory protocols. Therefore, the use of an integrated immunohistochemical marker panel combined with macroscopic findings, conventional histopathology, and clinical data is recommended within the diagnostic workflow of sudden cardiac death. In Indonesia, the implementation of postmortem IHC remains limited; nevertheless, it holds significant potential as a diagnostic adjunct when applied selectively and in a standardized manner within forensic practice.